A 0.54-0.55 THz 2×4 coherent source array with EIRP of 24.4 dBm in 65nm CMOS technology - Yan Zhao; Hsin-Chia Lu; Hong-Pei Chen; Yu-Teng Chang; Rulin Huang; Huan-Neng Chen; Chewnpu Jou; Fu-Lung Hsueh; Chang, Mau-Chung Frank (IEEE MTT-S International Microwave Symposium digest, 2015)
This paper presents a monolithically integrated 2×4 coherent source array operating at 0.54-0.55 Tera-Hertz (THz) in 65nm digital CMOS technology. The source array contains 20 oscillating elements which can radiate in-phase THz signal via each of their own differential slot ring antennas. Each of the oscillating elements is made of a triple-pushed Colpitts voltage controlled oscillator (TPCVCO). Among these oscillating elements, 16 are used for radiation source cores and 4 are used for synchronization bridges. The source array is tested to radiate 61 and 126 μW peak power near 0.55 THz by consuming 0.5 and 1.3W DC power, respectively. According to measured antenna directivity of 36.4dBi and simulated radiation efficiency of 50%, source array's Equivalent Isotropically Radiated Power (EIRP) can be estimated as 21.2 and 24.4 dBm, respectively. The output spectrum can also be tuned from 0.54 to 0.55 THz by varying the transistor bulk voltage. The measured phase noise is -79dBc/Hz at 1 MHz offset. To the best of our knowledge, this is the 1st coherent THz source made of monolithically integrated silicon IC technology beyond 0.5 THz.